Nursing research and evidence-based practice : ten steps to success - Keele, Rebecca (Sudbury, MA : Jones & Bartlett Learning, 2011)
"Nursing Research and Evidence-Based Practice: Ten Steps to Success offers a unique approach to learning about nursing research, particularly evidence-based nursing practice. It is ideal for nursing students and practicing nurses who need to understand the language and significance of research and how to translate it into evidence-based practice. This innovative text provides a step-by-step guide on how to develop evidence-based practice proposals for the real world and focuses on analyzing all forms of evidence. With chapter objectives, tables, algorithms, and real-life examples of full evidence-based nursing practice proposals, Nursing Research and Evidence-Based Practice: Ten Steps to Success is the essential "how-to" reference."--BOOK JACKET
Beginning tips on surviving nursing research and evidence-based nursing practice -- The quantitative research process -- Quantitative versus qualitative research or both? -- Data analysis -- Implementing evidence-based nursing practice : an overview -- Reading and critically analyzing empirical research studies -- Now it's your turn to analyze research -- Ethics in research and evidence-based nursing practice -- Evidence-based nursing practice projects : putting it all together -- Planned change in evidence-based nursing practice
Includes bibliographical references and index
Keywords: Nursing -- Research; Evidence-based nursing; Nursing Research -- methods; Evidence-Based Nursing; Research Design